Implementing a Quran Tahfidz Program in Aisyiyah Bustanul Athfal Kindergarten: Implementasi Program Tahfidz Quran di Tk Aisyiyah Bustanul Athfal - Rusmini, Endang; rindaningsih , Ida (Universitas Muhammadiyah Sidoarjo, 2024)
The importance of early Quranic education has gained recognition in fostering a generation that values religious texts. However, there remains a gap in understanding the structured development of Quran Tahfidz programs in kindergartens. This study aims to detail the Development of the Quran Tahfidz Program at Aisyiyah Bustanul Athfal 1 Candi Kindergarten, focusing on learning planning, implementation, and evaluation. Utilizing a qualitative approach and descriptive research methodology, data were collected through observations, interviews, and documentation studies. Results indicate that the program operates effectively, supported by the principal and teachers, emphasizing the importance of early memorization of the Quran. Continuous evaluation of planning, implementation, and factors affecting the program will be essential for enhancing graduate quality, ensuring proficient memorization and reading skills for higher educational levels. This research highlights the novelty of integrating structured Tahfidz programs in early childhood education, with implications for fostering a lifelong appreciation for the Quran among young learners. Ultimately, the study aims to contribute to the establishment of educational frameworks that promote Quranic memorization from an early age, nurturing a generation committed to their faith. Highlights: Structured Approach: The program involves careful planning, implementation, and evaluation to ensure effectiveness in Quranic education. Community Support: Successful execution relies on the backing of school leadership and teachers, highlighting the importance of collaborative efforts. Continuous Improvement: Ongoing assessment of the program’s components aims to enhance memorization skills and quality of graduates. Keywords: Quran, Tahfidz Program, Early Childhood Education, Aisyiyah Bustanul Athfal, Curriculum Development